Exploring Women’s Migration from Ukraine to Other Countries from the end of the 1980s to the 2020s - Oksana Koshulko (Randwick International of Social Science Journal, 2020)
The paper presents the results of research concerning women’s migration from Ukraine from the end of the 1980s to the 2020s. The paper considers two types of female migration, based on different motives, reasons, outcomes, and means to achieve the realization of their migration plans. The methodology of the paper consists of primary and secondary sources of information. The two types of female migration explored are those taking place in the 1980s and those in the 2020s. The first wave of female migration from Ukraine, from the end of the 1980s to 2000, has been called ‘women attempting to migrate through despair’ and the second wave, from 2000 to 2020, has been called ‘attempts by women to migrate due to need and danger’.